2021
DOI: 10.1093/jbi/wbab002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Breast Imaging Practice Operations and Recovery Efforts: A North American Study

Abstract: Objective To assess the impact of the COVID-19 pandemic on breast imaging facilities’ operations and recovery efforts across North America. Methods A survey on breast imaging facilities’ operations and strategies for recovery during the COVID-19 pandemic was distributed to the membership of the Society of Breast Imaging and National Consortium of Breast Centers from June 4, 2020 to July 14, 2020. A descriptive summary of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These guidelines advocated for strategies to shift the risk/benefit ratio for patients to facilitate a safe return to screening practices. In response, practices adopted a wide variety of strategies to encourage patients to return, including expanding hours, switching to electronic intake forms, improved cleaning and sanitation practices, and rearranging the workflows of clinics [ 12 ]. Several publications using regional and limited national data sets reported that in the months after the pandemic peak, screening mammography volumes began to rebound, but rates had not yet returned to prepandemic baseline [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines advocated for strategies to shift the risk/benefit ratio for patients to facilitate a safe return to screening practices. In response, practices adopted a wide variety of strategies to encourage patients to return, including expanding hours, switching to electronic intake forms, improved cleaning and sanitation practices, and rearranging the workflows of clinics [ 12 ]. Several publications using regional and limited national data sets reported that in the months after the pandemic peak, screening mammography volumes began to rebound, but rates had not yet returned to prepandemic baseline [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Breast radiologists may be particularly at risk, given their close emotional and physical contact with patients combined with limited remote working options compared with other radiology subspecialists. Screening mammography experienced one of the greatest imaging volume declines during the initial disease surge, putting breast radiologists at greater risk for redeployment, furloughs, and job loss and potentially further contributing to stress and financial instability [14,15]. In addition, unlike radiology in general, breast imaging is a female-dominated subspecialty, and the pandemic has been shown to affect women disproportionately in terms of job loss, childcare responsibilities, and mental health [16,17].…”
Section: Introductionmentioning
confidence: 99%